Study of Geometrical and Electronic Effects Induced by Hydrogen Chemisorption on Supported Pt Particles : Analysis of Pt-H EXAFS and Pt-H Anti-Bonding State Shape Resonances - Koningsberger, D.C.; Oudenhuijzen, M.K.; Bitter, J.H.; Ramaker, D.E. (Springer Science+Business Media, 2000)
Geometrical and electronic effects induced by hydrogen chemisorption on supported Pt particles are studied by analysing the PtH anti-bonding shape resonance. The fundamental principles of a new analysis method of the L2 and L3 X-ray absorption edges are summarised. The method is used for studying the PtH bonding properties of weakly and strongly bonded hydrogen on surfaces of supported metal catalysts. Also the interaction of hydrogen with a Pt/CeO2 catalyst as a function of the reduction temperature is investigated. The new analysis method makes it possible to follow the changes in the electronic structure of a Pt/Al2O3 catalyst as a function of the metal particle size.
Keywords: Scheikunde